Incidents of the labor informality in the commercial sector of Tulcan - Ipiales. - Miranda Realpe, Jorge Humberto; Hernández Delgado, Lizeth; Leyton Balseca, Gabriela (SATHIRI, 2020)
TThis research article aims to determine the factors that affect labour informality in the commercial sector of Tulcán-Ipiales. The approach used was qualitative and quantitative, the types of research: field, non-experimental, bibliographic, descriptive, documentary; for the surveys it was classified by more representative sectors of the traders of Tulcán and Ipiales; Sampling as a convenience, a total of 82 surveys were determined for Tulcán and 126 for Ipiales. The variable informality of the labor is related to the commercial sector, establishing topics such as the socioeconomic aspect of workers, market structure and labour regulation. It is determined that the socio-economic aspects of an informal worker at the border have to do with: educational level, economic burden, gender, age. In addition, legal limitations and lack of state support, it obliges local owners not to tax and not legalize their employees, also considering themselves as informal it work.